Phase Behaviour and Miscibility Studies of Collagen/Silk Fibroin Macromolecular System in Dilute Solutions and Solid State - Ghaeli, I (2017)
Miscibility is an important issue in biopolymer blends for analysis of the behavior of polymer pairs through the detection of phase separation and improvement of the mechanical and physical properties of the blend. This study presents the formulation of a stable and one-phase mixture of collagen and regenerated silk fibroin (RSF), with the highest miscibility ratio between these two macromolecules, through inducing electrostatic interactions, using salt ions. For this aim, a ternary phase diagram was experimentally built for the mixtures, based on observations of phase behavior of blend solutions with various ratios. The miscibility behavior of the blend solutions in the miscible zones of the phase diagram was confirmed quantitatively by viscosimetric measurements. Assessing the effects of biopolymer mixing ratio and salt ions, before and after dialysis of blend solutions, revealed the importance of ion-specific interactions in the formation of coacervate-based materials containing collagen and RSF blends that can be used in pharmaceutical, drug delivery, and biomedical applications. Moreover, the conformational change of silk fibroin from random coil to beta sheet, in solution and in the final solid films, was detected by circular dichroism (CD) and Fourier transform infrared spectroscopy (FTIR), respectively. Scanning electron microscopy (SEM) exhibited alterations of surface morphology for the biocomposite films with different ratios. Surface contact angle measurement illustrated different hydrophobic properties for the blended film surfaces. Differential scanning calorimetry (DSC) showed that the formation of the beta sheet structure of silk fibroin enhances the thermal stability of the final blend films. Therefore, the novel method presented in this study resulted in the formation of biocomposite films whose physico-chemical properties can be tuned by silk fibroin conformational changes by applying different component mixing ratios.